2008
DOI: 10.1177/0142723707087736
|View full text |Cite
|
Sign up to set email alerts
|

Learning to talk in a gesture-rich world: Early communication in Italian vs. American children

Abstract: Italian children are immersed in a gesture-rich culture. Given the large gesture repertoire of Italian adults, young Italian children might be expected to develop a larger inventory of gestures than American children. If so, do these gestures impact the course of language learning? We examined gesture and speech production in Italian and US children between the onset of first words and the onset of two-word combinations. We found differences in the size of the gesture repertoires produced by the Italian vs. th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
131
2
9

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(146 citation statements)
references
References 39 publications
3
131
2
9
Order By: Relevance
“…In particular, the representational gestures produced by Italian children included several object/action gestures (e.g., EATING) and attributive gestures (e.g., BIG), whereas American children almost exclusively produced conventional gestures (e.g., HI, YES). Despite these differences in gesture vocabulary, in both cultures gesture/speech combinations reliably predicted the onset of two-word combinations (Iverson et al 2008). These authors concluded that culture and adult input may influence to some extent how the manual modality is used for representational purposes.…”
Section: Cross Cultural Studies On the Use Of Gesture In Toddlersmentioning
confidence: 94%
See 1 more Smart Citation
“…In particular, the representational gestures produced by Italian children included several object/action gestures (e.g., EATING) and attributive gestures (e.g., BIG), whereas American children almost exclusively produced conventional gestures (e.g., HI, YES). Despite these differences in gesture vocabulary, in both cultures gesture/speech combinations reliably predicted the onset of two-word combinations (Iverson et al 2008). These authors concluded that culture and adult input may influence to some extent how the manual modality is used for representational purposes.…”
Section: Cross Cultural Studies On the Use Of Gesture In Toddlersmentioning
confidence: 94%
“…One study conducted on three American and three Italian children, followed longitudinally between the ages of 10 and 24 months (Iverson et al 2008), reported more frequent production of representational gestures by Italian children than by their American peers. In particular, the representational gestures produced by Italian children included several object/action gestures (e.g., EATING) and attributive gestures (e.g., BIG), whereas American children almost exclusively produced conventional gestures (e.g., HI, YES).…”
Section: Cross Cultural Studies On the Use Of Gesture In Toddlersmentioning
confidence: 99%
“…At 12 months, gestures, specially pointing, and prelexical vocalizations coordination can facilitate the development or the first lexical forms. Then, the coordination of the first lexical forms (words and protowords) with gestures in multimodal communicative patterns results predictive of later specific linguistic achievements (Goldin-Meadow, 1998;Iverson, et al, 2008;Iverson & Goldin-Meadow, 2005;Özçaliskan & Goldin-Meadow, 2005b). For example, when gesture and word convey complementary meanings, the answer obtained from the caregiver seems to facilitate the development of two-word combinations (GoldinMeadow et al, 2007).…”
mentioning
confidence: 99%
“…Ainda sobre o gesto de apontar, autores (Goldin-Meadow, 2009;Iverson, Capirci, Volterra, & Goldin-Meadow, 2008;Nogueira, 2009;Tomasello, 1999Tomasello, , 2003Volterra et al, 2004;Vygotsky, 2007) esclarecem que ele é um preditor da capacidade linguística, por promover o crescimento do aprendizado de palavras, auxiliado pelos rótulos utilizados pelos pais dos objetos para onde o bebê aponta. Assim, os bebês que já usam o gesto de apontar podem, por meio das interações, estar expostos a novas condições para seu próprio desenvolvimento vocabular.…”
Section: Ll Nunes and Fsb Aquinounclassified